The effect of caries excavation methods on the bond strength of etch‐and‐rinse and self‐etch adhesives to caries affected dentine. (December 2013) - Aggarwal, V; Singla, M; Yadav, S; Yadav, H
Abstract Background The aim of this study was to evaluate the influence of chemomechanical caries removal and conventional caries excavation on the microtensile bond strength of three different dentine adhesive systems. Methods Thirty extracted human mandibular molars with radiographic signs of dental caries extending up to the middle third of dentine were sectioned longitudinally through the centre of the carious lesion in a buccolingual direction to yield two sections. One half of each tooth was excavated by tungsten carbide bur and the other half was chemomechanically treated with Carisolv®. Three dentine bonding systems: an etch‐and‐rinse single bottle adhesive (Single Bond, 3M ESPE); a two bottle, two‐step self‐etch bonding system (One Coat Self Etching Bond, Coltene Whaledent); and a single‐step, single bottle self‐etch adhesive (Adper Easy Bond Self‐Etch Adhesive, 3M ESPE) were applied and composite build‐up was done. The specimens were tested for microtensile bond strength. Data were analysed using two‐way analysis of variance and pair‐wise multiple comparisons were done using the Holm–Sidak method. Results The etch‐and‐rinse adhesive and two bottle self‐etch system showed significantly higher bond strength than the single bottle self‐etch system. Caries excavation method had no influence on bond strength values. Conclusions Carisolv® did not affect the microtensile bond strength values of different adhesive systems tested to the caries affected dentine.